Factores criminológicos que inciden para el cometimiento de estafas financieras en la provincia de Chimborazo - Peñafiel Quinchuela, Manuel Vladimir (2025)
In this scientific article "Criminological Factors that Influence the Commitment of Financial Fraud in the Province of Chimborazo" tackles the current problem of financial scams in this province in 2024 where this research is important since today financial scams seriously affect the local economy and community confidence. The study is justified by the need to identify criminological factors, such as lack of financial education, economic vulnerability and family disintegration, which facilitate these crimes. On the other hand, the general objective is to analyze these factors to better understand the conditions that stimulate financial scams in Chimborazo, through interviews with experts in criminal law and criminology, we seek to obtain a detailed view of the criminal dynamics and their causes. The expected result is the formulation of specific recommendations, including the implementation of educational programs and the improvement of public policies, to prevent and reduce the incidence of financial fraud in the region. These measures aim to create a safer and more equitable environment for the inhabitants of Chimborazo, thus strengthening economic and social security in the province.